How often should percutaneous gastrostomy feeding tubes be replaced? A single-institute retrospective study - Min Jung Park; Byung Hyo Cha; Joo Yeong Baeg; Sunpyo Lee; Eui Yong Jeon; Wafaa Salem Obaid Alsalami; Osama Mohamed Ibrahim Idris; Young Joon Ahn (BMJ Open Gastroenterology)
Objective Percutaneous gastrostomy (PG) is a common procedure that enables long-term enteral nutrition. However, data on the durability of individual tube types are insufficient. We conducted this study to compare the longevities and features of different PG tube types.Design We performed a 5-year retrospective analysis of patients who underwent endoscopic and radiologic PG-related feeding tube procedures. The primary and secondary outcomes were tube exchange intervals and revenue costs, respectively. Demographic factors, underlying diseases, operator expertise, materials used, and complication profiles were assessed.Results A total of 599 PG-related procedures for inserting pull-type PG (PGP), balloon-type PG (PGB), PG jejunal MIC* (PGJM; gastrojejunostomy type), and PG jejunal Levin (PGJL) tubes were assessed. On univariate Kaplan-Meier analysis, PGP tubes showed longer median exchange intervals than PGB tubes (405 days (95% CI: 315 to 537) vs 210 days (95% CI: 188 to 238); p<0.001). Larger PGB tubes diameters were associated with longer durations than smaller counterparts (24 Fr: 262 days (95% CI: 201 to NA), 20 Fr: 216 days (95% CI: 189 to 239), and 18 Fr: 148 days (95% CI: 100 to 245)). The PGJL tubes lasted longer than PGJM counterparts (median durations: 168 days (95% CI: 72 to 372) vs 13 days (95% CI: 23 to 65); p<0.001). Multivariate Cox proportional regression analysis revealed that PGJL tubes had significantly lower failure rates than PGJM tubes (OR 2.97 (95% CI: 1.17 to 7.53); p=0.022). PGB tube insertion by general practitioners was the least costly, while PGP tube insertion by endoscopists was 2.9-fold more expensive; endoscopic PGJM tubes were the most expensive at two times the cost of PGJL tubes.Conclusion PGP tubes require replacement less often than PGB tubes, but the latter are more cost-effective. Moreover, PGJL tubes last longer than PGJM counterparts and, owing to lower failure rates, may be more suitable for high-risk patients.